Intuitive mathematical economics series: Linear algebra techniques to measure business cycles - Tomás Marinozzi; Leandro Nallar; Sergio A. Pernice (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
Linear algebra is without a doubt a fundamental tool to deal with empirical economic problems. The goal of this paper is to use some of these techniques to treat business cycles. To do that, we present the classic ordinary least square approach to estime the coefficients of a detrended time series in addition to the matrix form of the Hodrick-Prescott (HP) filter. This is a paper is part of "Intuitive Mathematical Economic Series".
Keywords: 330; Linear Algebra; business cycles; trend